The Effectiveness of Slum Settlement Arrangement in Mentaos Village, Banjarbaru City - Akbar, Dhiya'ul; Mursadin, Aqli (Technium Social Sciences Journal, 2022)
Mentaos area of Banjarbaru City South Kalimantan is one of the priorities for planning and slum settlement arrangement conducted by government of Banjarbaru City. The activities of slum setup in Banjarbaru City are one of priority programs conducted by government of Banjarbaru City that not only aiming to repair slum settlement infrastructure but also striving in realization of the area design so that can change the mindset or behaviour of society in slum settlement and also increasing the society’s economy. The aims, which are intended to be achieved in this research, are to examine the effectiveness of the implementation in handling slum settlement in Mentaos Urban Village, Banjarbaru City and to determine the approach that can ensure the effectiveness of the handling implementation of the slum settlement in Mentaos Urban Village, Banjarbaru City. The method used in this research is descriptive with a quantitive approach, the research result of The Effectiveness of Slum Settlement Arrangement in Mentaos Urban Village Banjarbaru City by distributing questionnaires is 68, 92 percent and specified as Effective. The final result that can be obtained from this research is that the efforts to deal with slums have been effective, then it is just a matter of maintaining the existing ones or increasing them in the future.